2020
DOI: 10.3390/pathogens9070564
|View full text |Cite
|
Sign up to set email alerts
|

Mosquito Mycobiota: An Overview of Non-Entomopathogenic Fungal Interactions

Abstract: The growing expansion of mosquito vectors leads to the emergence of vector-borne diseases in new geographic areas and causes major public health concerns. In the absence of effective preventive treatments against most pathogens transmitted, vector control remains one of the most suitable strategies to prevent mosquito-borne diseases. Insecticide overuse raises mosquito resistance and deleterious impacts on the environment and non-target species. Growing knowledge of mosquito biology has allowed the development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(65 citation statements)
references
References 80 publications
2
63
0
Order By: Relevance
“…Isolating microorganisms from these two organs could provide insights into their metabolic and physiological properties as well as their potential contribution for the mosquito host. Interestingly, recent studies highlighted that live bacteria and fungi, which are associated with mosquitoes, are able to stimulate larval growth only when viable and present above a certain density [29,30]. It was also shown that mosquitoes could survive in the absence of a living microbiota, suggesting that the gut living microbiota could favor mosquito physiological properties by participating in their nutrition [31].…”
Section: Taxonomic Composition Of Bacterial and Fungal Communities Inmentioning
confidence: 99%
“…Isolating microorganisms from these two organs could provide insights into their metabolic and physiological properties as well as their potential contribution for the mosquito host. Interestingly, recent studies highlighted that live bacteria and fungi, which are associated with mosquitoes, are able to stimulate larval growth only when viable and present above a certain density [29,30]. It was also shown that mosquitoes could survive in the absence of a living microbiota, suggesting that the gut living microbiota could favor mosquito physiological properties by participating in their nutrition [31].…”
Section: Taxonomic Composition Of Bacterial and Fungal Communities Inmentioning
confidence: 99%
“…Reports document existence of horizontal and transstadial transfer of symbionts from pupae to adult in mosquitoes [ 14 , 30 , 32 ]. It has been shown that some microbes are transstadially transmitted from larvae to adults [ 12 , 31 , 39 , 40 ], and that a shift from aquatic to terrestrial leads to midgut renewal that causes microbial reduction or elimination with the retention of essential microbes [ 24 , 41 ]. Other observations indicate that most symbionts are lost when pupae emerge to adult [ 23 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among a wide number of mosquito-associated yeasts ( Malassigné et al, 2020 ), W. anomalus is a promising candidate for SC strategies against malaria and possibly other MBDs. We summarize main features that support this finding: (i) it is a mutualistic symbiont in Anopheles , Aedes , and Culex mosquitoes (impling a stable association with vectors); (ii) it bypasses the fungal reduction during the mosquito metamorphosis and after the blood ingestion; (iii) it spreads by trans-stadial and vertical transmission routes (impling self-spreading among mosquitoes and reducing efforts and costs of delivery); (iv) it inhibits the malaria parasite in the vector mosquitoes suggesting that, thanks to the wide killer activity, it has potential to affect a broad spectrum of mosquito-borne pathogens (e.g., arboviruses); (v) it is considered safe for humans and the environment (EFSA authorizes use of killer strains); (vi) it is clinically not relevant and its killer effect is based on exo-β-1,3-glucanase enzymatic activities (which targets microbes but is harmless in mammalian cell); (vii) it can be ingested by larvae and adults as a food source (advantage of yeasts over intracellular symbionts such as Wolbachia ); and (viii) it can be formulated at low costs of production and released in the environment by dried-yeasts containing tablets, as recently carried out with fungal-larvicides used against Aedes spp.…”
Section: Wickerhamomyces Anomalus Is a Promising Tool For “Smentioning
confidence: 99%
“…The analysis of the mosquito-associated microbiota (bacteria, fungi, protists, viruses, and nematodes) is gaining attention since microbes are recognized to influence many traits of the mosquito biology, such as development, physiology, immunity, and vector competence ( Guégan et al, 2018 ). While an increasing number of studies have focused on bacteria, the fungal community (mycobiota) has been largely neglected, but recent studies show the presence of an important fungal diversity in mosquitoes ( Malassigné et al, 2020 ). Mosquito-mycobiota is mainly composed of Ascomycota, which comprise mostly species of Pezizomycotina and Saccharomycotina (subphyla); Pezizomycotina include species of filamentous fungi, whereas Saccharomycotina are basically represented by yeasts, such as Candida , Meyerozyma , Pichia , and Wickerhamomyces , that adapt to survive in the insect gut and different mutualistic yeast-insect symbioses based on trophic interdependence have been described ( Malassigné et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation